2022
DOI: 10.1101/2022.04.27.22274369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-Dimensional Multinomial Multiclass Severity Scoring of COVID-19 Pneumonia Using CT Radiomics Features and Machine Learning Algorithms

Abstract: We aimed to construct a prediction model based on computed tomography (CT) radiomics features to classify COVID-19 patients into severe-, moderate-, mild-, and non-pneumonic. A total of 1110 patients were studied from a publicly available dataset with 4-class severity scoring performed by a radiologist (based on CT images and clinical features). CT scans were preprocessed with bin discretization and resized, followed by segmentation of the entire lung and extraction of radiomics features. We utilized two featu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…And so on for all locations and all angular; see Figure 5. In the last step, the twenty-two texture features of the GLCM matrices we used to perform the proposed method are defined in Table 1 [10,18,19]. Where 𝑄 = ∑…”
Section: 𝑝(𝑟 𝑐|𝑑 𝜃) = 𝑁 𝑑𝜃 (𝑟 𝑐) 𝑁mentioning
confidence: 99%
“…And so on for all locations and all angular; see Figure 5. In the last step, the twenty-two texture features of the GLCM matrices we used to perform the proposed method are defined in Table 1 [10,18,19]. Where 𝑄 = ∑…”
Section: 𝑝(𝑟 𝑐|𝑑 𝜃) = 𝑁 𝑑𝜃 (𝑟 𝑐) 𝑁mentioning
confidence: 99%
“…Several studies have demonstrated high sensitivity of chest CT for COVID-19 detection, with reports suggesting that CT abnormalities may precede positive virological assay results [ 4 , 5 ]. Chest CT also allows physicians to assess the pathological condition of the lungs, stage the disease, and formulate a treatment plan for the patient [ 6 ]. Not surprisingly, interest in chest CT for diagnosing and managing COVID-19 patients has grown apace.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies concerning quantitative radiomics analysis, through acting as biomarkers, have provided new insights into better handling of diseases, such as cancer [24] and coronary artery disease (CAD) to predict survival [25,26], prognosis [27,28], and therapeutic response [29,30], different pathology classification [28,[31][32][33], and accumulating data for personalized medicine [34]. In fact, radiomics is an almost new science that has attracted many researchers' attention and is therefore growing rapidly.…”
Section: Introductionmentioning
confidence: 99%